2022
DOI: 10.21203/rs.3.rs-2284572/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations between the serum triglyceride-glucose index and pericoronary adipose tissue attenuation and plaque features using dual-layer spectral detector computed tomography: a cross- sectional study

Abstract: Background: The triglyceride-glucose (TyG) index is an independent predictor of coronary artery disease (CAD). However, the relationships between the TyG index, pericoronary adipose tissue (PCAT), and atherosclerotic plaque characteristics remain unclear. Therefore, this study investigated these associations. Methods: We retrospectively collected data on patients with chest pain who underwent coronary computed tomography angiography using spectral detector computed tomography at our institution from June 2021 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…This is attributed to our patient selection, as we included patients with single plaques in their coronary arteries, mostly nonobstructive, and in the early stages of coronary atherosclerosis. This study suggests that changes in vascular inflammation detectable in the early stages of atherosclerosis precede changes in atherosclerotic plaques 17 .…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This is attributed to our patient selection, as we included patients with single plaques in their coronary arteries, mostly nonobstructive, and in the early stages of coronary atherosclerosis. This study suggests that changes in vascular inflammation detectable in the early stages of atherosclerosis precede changes in atherosclerotic plaques 17 .…”
Section: Discussionmentioning
confidence: 55%
“…The results showed that positive remodeling was independently and positively correlated with abnormal FAI value, which is consistent with previous studies. 17 In the early to middle stage of atherosclerosis development, positive remodeling reflects the degree of compression exerted on the vascular wall and endothelium by the lateral growth of the plaque, leading to damage to the vascular endothelial cells (VECs). This, in turn, stimulates VECs to express vascular cell adhesion molecules, promoting the adhesion of monocytes, T cells, and other cells to VECs.…”
Section: Discussionmentioning
confidence: 99%
“…6 As an alternative to the conventional gold standard hyperinsulinemic-euglycemic clamp method, the TyG index was introduced as a more simple and cost-effective means of IR with high sensitivity (96.5%) and specificity (85%). 14 Currently, the TyG index has been extensively explored in diverse medical issues, such as cardiovascular disease, [6][7][8][9] arterial stiffness progression, 10 diabetic nephropathy, 11 new-onset hypertension, 15 cardiometabolic diseases, 16 DM, [17][18][19] intensity care unit mortality, 20 obesity, 21 and hearing impairment. 22 However, there are relative few reports about TyG index and hypertensive nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the triglyceride glucose (TyG) index has emerged as a non-invasive and cost-effective alternative indicator to assess IR. 5 Recent studies have shown that an elevated TyG index is associated with an increased risk of cardiovascular disease, [6][7][8][9] arterial stiffness progression, 10 and diabetic nephropathy. 11 However, evidence supporting the association between the TyG index and hypertensioninduced renal injury remains limited.…”
Section: Introductionmentioning
confidence: 99%